Application of a Co4N lactic acid-specific nanoscale enzyme rich in nitrogen vacancies in lactic acid detection
Patent Information
- Application Number
- CN202611073396.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]基于上述分析,本发明提供了一种富含氮空位的Co4N纳米酶(Co4N-Nv)及其制备方法,以解决现有纳米酶底物选择性差和天然酶稳定性差的双重技术瓶颈
[0025](1)本发明首次在Co4N纳米酶中引入氮空位,通过几何预组织与底物诱导动态电子调控的协同作用,赋予纳米酶对乳酸的高度底物特异性,其选择性与天然LOx相当,突破了现有纳米酶选择性不足的瓶颈。
Smart Images

Figure CN122895022A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanozyme preparation and nanobiosensing technology, specifically relating to the application of a nitrogen-vacancy-rich Co4N lactate-specific nanozyme in lactate detection. Background Technology
[0002] Natural LOx (L-lactic acid oxidase) is the standard biorecognition element in the field of lactate sensing. However, the inherent poor stability, high preparation cost, and harsh storage conditions of LOx severely restrict its development in long-term applications. Nanozymes, as a class of nanomaterials with enzyme-like catalytic activity, have become a powerful alternative to natural enzymes, but poor substrate selectivity remains a common bottleneck restricting their development, making it difficult for them to truly replace natural enzymes in biosensing systems.
[0003] Lactic acid, as an important biomarker, can dynamically reflect the body's metabolic activities, exercise intensity, and physiological state, and has significant detection value in clinical diagnosis, sports medicine, and daily health monitoring. Currently, LOx is the standard biometric element in the field of lactic acid sensing. It catalyzes the oxidation of lactic acid to H2O2, and achieves sensitive and accurate analysis of lactic acid through quantitative detection of H2O2. However, the inherent poor stability, high preparation cost, and harsh storage conditions of natural enzymes severely restrict their development in biosensing applications. Nanozymes, as a class of nanomaterials with enzyme-like catalytic activity, have become a powerful alternative to natural enzymes due to their excellent stability, scalable preparation, and compatibility with flexible platforms. Although the catalytic activity of nanozymes has made significant progress in recent years, poor substrate selectivity remains a common bottleneck restricting their development, making it difficult for them to truly replace natural enzymes in biosensing systems.
[0004] Current lactate-responsive nanozymes are primarily designed using a structure-based biomimetic paradigm, replicating the geometric features of the active site of natural enzymes through engineered atomic coordination environments. While this strategy effectively enhances catalytic activity, the understanding of the substrate-specific mechanisms of natural enzymes remains insufficient. Taking lactate oxidase as an example, its excellent selectivity stems not only from the geometric complementarity of the active pocket but, more importantly, from the dynamic electronic adaptation process induced by substrate binding: upon entering the active pocket, lactate triggers a continuous rearrangement of the electron density around the flavin mononucleotide cofactor, thereby specifically stabilizing the deprotonation of the lactate α-CH bond. This electronic rearrangement process exhibits high substrate specificity—lactate can induce this response, while structurally similar interfering substances cannot elicit the same electron repositioning. This substrate-induced electronic plasticity is the core mechanism for the high selectivity of lactate oxidase. In contrast, most existing lactate-responsive nanozymes are limited to static structural replication and lack the ability to mimic such electronic responses. Therefore, although their catalytic activity may approach or even surpass that of natural enzymes, their substrate selectivity remains limited, severely restricting their application in complex biological fluids. Overcoming this bottleneck requires, on the basis of precise geometric construction, endowing materials with the ability to sense and respond to substrate-induced electronic rearrangements. Only by combining structural precision with adaptive electronic functions can we hope to approach the selectivity level of natural lactate oxidase.
[0005] Therefore, this invention is the first to attempt to design a nanozyme, Co4N-Nv, specifically for oxidizing lactic acid. This nanozyme not only reproduces the geometry of LOx but also mimics its substrate-induced dynamic electronic regulation mechanism, thereby achieving selective oxidation of lactic acid. Co4N-Nv can catalyze the oxidation of lactic acid to pyruvate and H2O2, with catalytic specificity comparable to that of natural LOx. By combining lactic acid oxidation with the electrochemical reduction of in-situ generated hydrogen peroxide, this invention further develops an electrochemical sensing platform for lactic acid, enabling continuous monitoring of lactic acid in sweat, with a detection limit (0.065 mM) 5.14 times lower than that of LOx-based methods. Summary of the Invention
[0006] Based on the above analysis, this invention provides a nitrogen-vacancy-rich Co4N nanozyme (Co4N-Nv) and its preparation method, thereby overcoming the dual technical bottlenecks of poor substrate selectivity and poor stability of natural enzymes in existing nanozymes. Another objective of this invention is to provide a sweat lactic acid sensor and lactic acid detection method based on this nanozyme, enabling real-time, continuous, and non-invasive precise monitoring of lactic acid in sweat.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] The present invention first provides a nitrogen-vacancy-rich Co4N nanozyme (Co4N-Nv), which has a nanocubic morphology and is rich in nitrogen vacancies in its lattice. It can specifically catalyze the oxidation of lactate to produce pyruvate and hydrogen peroxide. Its substrate selectivity is comparable to that of natural lactate oxidase, and its catalytic activity and stability are significantly better than those of natural enzyme.
[0009] This invention also discloses a method for preparing Co4N-Nv nanozymes, comprising the following steps:
[0010] (1) Dissolve 280.5 mg of cobalt acetate Co(CH3COO)2·4H2O in 150 mL of deionized water and stir for 10 min to obtain solution A;
[0011] (2) Dissolve 199.5 mg potassium ferricyanide K3[Fe(CN)6] and 4.5 g polyvinylpyrrolidone (PVP) in 150 mL of deionized water and stir for 30 min to obtain solution B;
[0012] (3) Solution A was slowly added dropwise to solution B. The mixed solution turned pink and was stirred at room temperature for 24 h. The product was then centrifuged (11,000 rpm), washed three times with deionized water, and dried under vacuum at 60 °C overnight to obtain the Prussian blue analog precursor.
[0013] (4) The obtained Prussian blue analogue precursor was placed in a porcelain boat and heated to 450 °C at a rate of 5 °C / min in a tube furnace and kept at 450 °C for 1 h under N2 flow.
[0014] (5) Then the temperature was increased to 500 °C at a rate of 1 °C / min, and the gas flow was immediately switched to NH3. The reaction continued for 2 h under the NH3 atmosphere.
[0015] (6) After the reaction was completed, the atmosphere was restored to N2 and cooled to room temperature; then it was heated at 400 °C for 2 h in an Ar / H2 mixed atmosphere with a volume fraction of H2 of 5%–10% and a heating rate of 5 °C / min to obtain a nitrogen-vacancy-rich Co4N nanozyme, denoted as Co4N-Nv.
[0016] The present invention also discloses the application of the above-described Co4N-Nv nanozyme as a lactate oxidase mimic in the catalytic oxidation of lactate.
[0017] The present invention also discloses a sweat lactic acid sensor, the sensor comprising:
[0018] The device comprises a working electrode, a reference electrode, and a counter electrode, wherein the surface of the working electrode is sequentially modified with a Prussian blue (PB) electron mediator layer, a Co4N-Nv nanozyme catalytic layer, and a chitosan (CS) protective layer.
[0019] Furthermore, the Prussian blue electron mediator layer was obtained by cyclic voltammetry deposition, with the deposition solution being a mixed solution containing 2.5 mM FeCl3, 2.5 mM K3Fe(CN)6, 100 mM KCl and 100 mM HCl, the scan rate being 50 mV / s and the number of scan cycles being 20.
[0020] Furthermore, the Co4N-Nv nanozyme catalytic layer was prepared by drop coating, with a drop coating amount of 2 µL, a concentration of 4 mg / mL, and a solvent of 0.1 M pH 7.4 phosphate buffer; the chitosan protective layer was formed by drop coating 3 µL of 1 wt% chitosan solution, with 2 wt% acetic acid as the solvent.
[0021] The present invention also discloses a method for detecting lactic acid, which uses the sweat lactic acid sensor to determine the quantitative relationship between the current response value and the lactic acid concentration by recording the current-time (it) curve, thereby realizing the electrochemical detection of lactic acid.
[0022] Furthermore, the test samples include sweat and other tissue fluids containing lactic acid, with a detection limit of 0.065 mM and a linear range of 5-30 mM;
[0023] The electrochemical detection was performed in 0.1 M pH 7.4 phosphate buffer at a detection potential of 0.05 V.
[0024] The beneficial effects of this invention are as follows:
[0025] (1) This invention introduces nitrogen vacancies into Co4N nanozymes for the first time. Through the synergistic effect of geometric pre-organization and substrate-induced dynamic electronic regulation, the nanozymes are endowed with high substrate specificity for lactate. Their selectivity is comparable to that of natural LOx, breaking through the bottleneck of insufficient selectivity of existing nanozymes.
[0026] (2) The Co4N-Nv nanozyme of the present invention has excellent lactate oxidase-like catalytic activity, and its catalytic constant (K) is very high. cat It has higher levels of natural LOx and no vacancy-free Co4N, and can efficiently catalyze the oxidation of lactic acid and release H2O2 in situ under mild conditions.
[0027] (3) The Co4N-Nv nanozyme described in this invention has excellent stability and can still maintain more than 80% of its enzyme-like activity after 5 cycles, which is significantly better than natural LOx and is suitable for long-term continuous monitoring.
[0028] (4) The detection limit of the sweat lactic acid sensor based on Co4N-Nv is as low as 0.065 mM, which is about 5.14 times higher than that of the natural LOx-based sensor. It has a wide linear range, fast response, and strong anti-interference ability, and can realize real-time, continuous, non-invasive and accurate detection of lactic acid in sweat.
[0029] (5) The preparation method provided by the present invention is simple, low-cost, and highly reproducible, and is easy to scale up for production. Attached Figure Description
[0030] Figure 1 This is a flowchart of the preparation process of Co4N-Nv.
[0031] Figure 2 This is a transmission electron microscope image of Co4N-Nv.
[0032] Figure 3 The image shows the electron paramagnetic resonance spectrum of Co4N-Nv.
[0033] Figure 4 (a) is the absorption spectrum of lactic acid oxidation catalyzed by LOx, Co4N-Nv and Co4N; Figure 4 (b) K for LOx, Co4N-Nv and Co4N cat Value comparison.
[0034] Figure 5 The selectivity of Co4N-Nv and LOx for small biomolecules.
[0035] Figure 6 For the stability comparison of Co4N-Nv and LOx.
[0036] Figure 7 The response of the lactate sensor based on (a) Co4N-Nv and (b) LOx to lactate is shown. The inset shows the corresponding calibration curves.
[0037] Figure 8 This study describes the response of a Co4N-Nv-based lactic acid sensor to lactic acid in the sweat of a subject. Detailed Implementation
[0038] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications and variations to the present invention without departing from its spirit, and all such modifications and variations should be included within the scope of protection of the present invention.
[0039] Example 1
[0040] See attached document Figure 1As shown, the precursor was prepared by coprecipitation and then subjected to temperature-programmed gas-phase nitridation-reduction treatment to obtain Co4N-Nv.
[0041] Preparation of Co4N-Nv nanozymes
[0042] 280.5 mg of cobalt acetate (Co(CH3COO)2·4H2O) was dissolved in 150 mL of deionized water and magnetically stirred for 10 min to obtain a clear pink solution A. Separately, 199.5 mg of potassium ferricyanide (K3[Fe(CN)6]) and 4.5 g of polyvinylpyrrolidone (PVP, molecular weight approximately 40,000, morphology control agent) were added to 150 mL of deionized water and magnetically stirred for 30 min until completely dissolved to obtain solution B. Under continuous stirring, solution A was slowly added dropwise to solution B at a rate of 2–3 drops per second, and the mixed solution gradually turned a deep pink color. After the addition was complete, stirring was continued at room temperature (25 ± 2 ℃) for 24 h to allow the coprecipitation reaction to proceed fully. The reaction product was transferred to a centrifuge tube and centrifuged at 11,000 rpm for 10 min. The supernatant was discarded, and the solution was resuspended in deionized water and washed. This centrifugation-washing process was repeated three times to remove unreacted ions and surfactants. The washed precipitate was placed in a vacuum drying oven and dried overnight at 60 °C to obtain Prussian blue analogue (PBA) precursor powder.
[0043] The obtained PBA precursor powder was uniformly spread in a ceramic boat and placed in a tube furnace. Under a N2 atmosphere (flow rate 100 sccm), the furnace was heated to 450 °C at a heating rate of 5 °C / min and held at 450 °C for 1 h to allow the precursor to undergo preliminary carbonization and structural transformation. Subsequently, the temperature was further increased to 500 °C at a slower heating rate of 1 °C / min. Upon reaching 500 °C, the atmosphere was immediately switched to NH3 (flow rate 150 ml / min) and held for 2 h to carry out a gas-phase nitriding reaction, resulting in the formation of the Co4N phase. After the nitriding reaction was completed, the atmosphere was restored to N2, and the furnace was allowed to cool naturally to room temperature. Finally, in an Ar / H2 mixed atmosphere (H2 volume fraction 5%, flow rate 100 ml / min), the temperature was increased to 400 °C at a heating rate of 5 °C / min and held at that temperature for 2 h for reduction treatment. By selectively etching some nitrogen atoms in the lattice, abundant nitrogen vacancies were introduced into the Co4N lattice, and finally, a Co4N nanozyme rich in nitrogen vacancies was obtained, denoted as Co4N-Nv.
[0044] like Figure 2 The above-mentioned transmission electron microscope image of Co4N-Nv is shown. It can be seen from the image that Co4N-Nv has a nanocubic structure with an average diameter of approximately 160 nm. Figure 2 a). High-resolution transmission electron microscopy (HRTEM) images ( Figure 2b) shows that the lattice spacing of Co4N-Nv is 0.21 nm, corresponding to the (111) crystal plane of Co4N-Nv.
[0045] like Figure 3 The electron paramagnetic resonance spectrum of the above-mentioned Co4N-Nv is shown. Compared with Co4N, Co4N-Nv shows a significant resonance signal at g=2.004, indicating the presence of unpaired electrons, thus strongly confirming the successful construction of nitrogen vacancies.
[0046] Comparative Example 1
[0047] Preparation of vacancy-free Co4N nanozymes (Co4N) (Comparative Example)
[0048] As a comparative example, a vacancy-free Co4N nanozyme was prepared. The preparation method was the same as in Example 1, except that after the NH3 nitridation reaction, it was directly cooled to room temperature under a N2 atmosphere without subsequent Ar / H2 reduction treatment. The resulting product was designated Co4N and used as a control sample for subsequent activity, selectivity, and stability tests.
[0049] Application Example 1
[0050] Fabrication of a sweat lactic acid sensor
[0051] (1) Electrochemical deposition of Prussian blue (PB) electron mediator layer:
[0052] Laser-etched graphene (LEG) was used as the working electrode, with an effective electrode area of 7.065 mm². 2 A three-electrode system was constructed using Ag / AgCl (saturated KCl) as the reference electrode and platinum wire as the counter electrode. The deposition solution was a mixed solution containing 2.5 mM FeCl3, 2.5 mM K3Fe(CN)6, 100 mM KCl, and 100 mM HCl. Electrodeposition was performed using cyclic voltammetry (CV) at a scan rate of 50 mV / s, a potential window of 0–0.5 V (vs. Ag / AgCl), and 20 scan cycles. After deposition, the electrode surface was gently rinsed with deionized water and dried with nitrogen gas to obtain the PB / LEG electrode.
[0053] (2) Modification of the Co4N-Nv catalyst layer:
[0054] Co4N-Nv was dispersed in 0.1 M pH 7.4 PBS and sonicated for 20 min to prepare a homogeneous dispersion of 4 mg / mL. 2 µL of this dispersion was drop-coated onto the surface of a PB / LEG electrode and allowed to air dry at room temperature.
[0055] (3) Modification of the chitosan (CS) protective layer:
[0056] Chitosan was dissolved in a 2 wt% acetic acid solution to prepare a 1 wt% chitosan solution. 3 µL of this solution was drop-coated onto the surface of a Co4N-Nv / PB / LEG electrode to prevent nanozyme detachment. After drying at room temperature, a porous protective film was formed, yielding the CS / Co4N-Nv / PB / LEG sensor, denoted as the Co4N-Nv-based lactic acid sensor.
[0057] (4) Preparation of the control sensor:
[0058] Following the same method, a lactate sensor based on natural LOx was prepared by replacing Co4N-Nv with natural LOx (4 mg / mL, dissolved in 0.1 M pH 7.4 PBS), denoted as CS / LOx / PB / LEG sensor.
[0059] Application Example 2
[0060] Detection of lactate in subjects
[0061] To verify the effectiveness of the sensor in monitoring lactic acid concentration under skin contact and continuous sweating conditions, we wore the device on the arm of the subjects and monitored the lactic acid concentration in their sweat. The experiments involving human subjects in this study complied with ethical guidelines, and the protocol used was (No.: BO-CAI-2024-005). Furthermore, this experiment was approved by the Science and Technology Ethics Committee of the Analytical and Testing Center of Northeast Normal University and the Science and Technology Ethics Committee of Northeast Normal University. In studies involving human subjects, all subjects obtained written informed consent before participating in the study.
[0062] Experimental Example 1
[0063] Test method:
[0064] (1) Solvents and preparation methods for HRP and OPD:
[0065] HRP preparation method: Weigh 10 mg of HRP powder and dissolve it in 10 ml of water to obtain 1 mg / ml; take 100 μL of 1 mg / mL HRP stock solution and dilute it with 0.1 M pH 7.4 PBS to a final volume of 10 mL to obtain 0.01 mg / mL HRP working solution;
[0066] OPD preparation: Weigh 5.4 mg of OPD powder and dissolve it in 50 mL of aqueous solution to obtain 1 mM OPD.
[0067] (2) Absorbance measurement: Tecan Spark test wavelength 300-800 nm, optical path 1 cm;
[0068] (3) The Kcat value is calculated using the following formula:
[0069] Kcat = Vmax / [E];
[0070] Where Vmax is the maximum reaction rate; [E] is the molar concentration of Co catalytic sites on the nanozyme, determined by inductively coupled plasma optical emission spectrometry (ICP-OES);
[0071] The Vmax value was obtained as follows: First, 0.5 ml of 2 mg / ml Co4N-Nv, 1 ml of PBS, and 1 ml of lactic acid (0.5, 1, 5, 15, 50 mM) were added to centrifuge tubes. After mixing, the tubes were incubated at 37 ℃ with shaking for (5, 10, 15) minutes respectively. After centrifugation, 200 μL of the supernatant was transferred to a 96-well plate, and then 10 μL of 0.01 mg / ml HRP and 100 μL of LOPD were added. After reacting for 2 minutes, the absorbance (OD) of each group was measured at 450 nm using a microplate reader. 450 The Michaelis curve was obtained by plotting the calculated initial rate against the substrate concentration. The data points were then fitted according to the Michaelis equation (V = Vmax × [S] / (Km + [S])) to determine Vmax and the Michaelis constant (Km), where [S] is the lactic acid concentration.
[0072] (4) Definition of active unit: The amount of enzyme required to catalyze the conversion of 1 micromolar substrate into product per minute.
[0073] Control group 1 (natural LOx): Co4N-Nv was replaced with the same concentration of natural LOx, and all other conditions were the same.
[0074] Control group 2 (no vacancy Co4N): Co4N-Nv was replaced with the same concentration of Co4N, and all other conditions were the same.
[0075] Control group: The lactate solution was replaced with 0.1 M pH 7.4 PBS, and all other conditions were the same.
[0076] The results are as follows Figure 4 The results showed that the amount of H2O2 produced by the lactate oxidation catalyzed by Co4N-Nv was significantly higher than that of Co4N and natural LOx, indicating that Co4N-Nv has superior lactate oxidase activity. Figure 4 b shows that the Kcat value of Co4N-Nv is higher than that of Co4N and natural LOx.
[0077] Experimental Example 2
[0078] Substrate selectivity test
[0079] To evaluate the substrate selectivity of Co4N-Nv, common interfering substances in biological fluids were selected for testing, including: 170mM D-glucose, 50μM L-ascorbic acid (AA), 50μM uric acid (UA), and 25μM dopamine (DA).
[0080] Test method: First, add 0.5 ml of 2 mg / ml Co4N-Nv, 1 ml of PBS, and 1 ml of interfering substance to a centrifuge tube. Mix well and incubate at 37 ℃ with shaking for 10 minutes. After 10 minutes, centrifuge and transfer 200 μL of the supernatant to a 96-well plate. Add 10 μL of 0.01 mg / ml HRP and 100 μL of LOPD. After reacting for 2 minutes, use a microplate reader to measure the absorbance (OD) of each group at 450 nm. 450 ).
[0081] The results show that ( Figure 5 Co4N-Nv exhibits significant catalytic activity for lactic acid, but extremely low catalytic activity for the aforementioned interfering substances, and its selectivity pattern is highly similar to that of natural LOx.
[0082] Experimental Example 3
[0083] Stability test
[0084] Co4N-Nv and natural LOx were subjected to multiple cyclic catalytic tests to evaluate their operational stability.
[0085] Test method: First, add 0.5 ml of 2 mg / ml Co4N-Nv, 1 ml of PBS, and 1 ml of 5 mM lactate to a centrifuge tube. Mix well and incubate at 37 ℃ with shaking for 10 minutes. After 10 minutes, centrifuge and transfer 200 μL to a 96-well plate. Add 10 ml of 0.01 mg / ml HRP and 100 μL of LOPD. After reacting for 2 minutes, use a microplate reader to measure the absorbance (OD) of each group at 450 nm. 450 After centrifuging, the nanozymes are redispersed and the above steps are repeated.
[0086] The results show that ( Figure 6 After 5 cycles, Co4N-Nv still retains more than 80% of its initial activity, while the activity of natural LOx decreases to less than 60% of its initial activity.
[0087] Test Example 4
[0088] Electrochemical detection performance evaluation
[0089] The chronoamperometry (it) method was used to evaluate the sensor’s electrochemical response to lactic acid.
[0090] Test method: The prepared Co4N-Nv-based electrochemical sensor was placed in PBS, and the current response at a potential of 0.05V was recorded by adding different concentrations of lactic acid solution.
[0091] A calibration curve was plotted by plotting the current response value (100 s) against the lactic acid concentration (C). The results are as follows: Figure 7 As shown in figure a, the Co4N-Nv-based sensor exhibits good linearity in the range of 5–30 mM, with the linear equation being ΔI (µA·mm). -2 ) = -0.05893·C (mM) - 0.37575, correlation coefficient R 2 > 0.99. The limit of detection (LOD) was calculated based on 3σ / k (where σ is the standard deviation of the blank sample current and k is the slope of the calibration curve), yielding an LOD of 0.065 mM. The sensitivity (slope k divided by electrode area) was 0.132 µA·mM. -1 ·mm -2 .
[0092] Sensors based on natural LOx were tested using the same method. Figure 7 (b) Its linear range is 5–30 mM, and its LOD is 0.334 mM. The detection limit of the Co4N-Nv-based sensor is reduced by approximately 5.14 times compared to the LOx-based sensor, and its sensitivity is significantly improved.
[0093] In addition, we performed a correlation analysis between sweat lactate levels measured by Co4N-Nv and LOx-based lactate sensors and results obtained from commercial lactate detection kits. Figure 7 c). The results showed that the Co4N-Nv-based sensor had a high consistency with the experimental results (r=0.92), while the LOx-based sensor showed a weaker correlation (r=0.55). This comparison indicates that the Co4N-Nv-based sensor has higher accuracy in the quantitative analysis of sweat lactic acid.
[0094] Experimental Example 5
[0095] Detection of lactic acid in the sweat of the subjects.
[0096] An electrochemical sensor based on Co4N-Nv was placed on the subject's arm, and the response current at a potential of 0.05V was recorded. Figure 8 As shown, during the initial 10-minute rest period, a slow increase in lactate concentration was observed from 0 mM. Subsequently, when the subject began to move, the lactate concentration changed significantly, reaching 12 mM, indicating that the device is able to capture dynamic lactate fluctuations caused by physical activity.
Claims
1. A nitrogen-vacancy-rich Co4N nanozyme, which has a nanocubic morphology and contains nitrogen vacancies in its lattice, can specifically catalyze the oxidation of lactic acid to pyruvate and hydrogen peroxide, and has substrate selectivity for lactic acid comparable to that of natural lactate oxidase.
2. A method for preparing the Co4N-Nv nanozyme according to claim 1, comprising: (1) Dissolve 280.5 mg of cobalt acetate in 150 mL of deionized water to prepare solution A; (2) Dissolve 199.5 mg potassium ferricyanide and 4.5 g polyvinylpyrrolidone in 150 mL of deionized water to prepare solution B; (3) Solution A was slowly added dropwise to solution B, and the mixture was stirred at room temperature for 24 h. After centrifugation and washing at 11,000 rpm and vacuum drying at 60 °C, the Prussian blue analog precursor was obtained. (4) The precursor is heated to a first temperature at a first heating rate under a nitrogen atmosphere and held at that temperature, and then heated to a second temperature at a second heating rate, and immediately switched to an ammonia atmosphere to carry out the nitriding reaction. (5) After nitriding, the temperature is lowered to room temperature under inert gas protection, and then reduced at a third temperature in an Ar / H2 mixed atmosphere to obtain Co4N-Nv rich in nitrogen vacancies, which is Co4N-Nv nanozyme.
3. The preparation method according to claim 2, wherein: In step (4), the first heating rate is 5 ℃ / min, the first temperature is 450 ℃, and the holding time is 1 h; The second heating rate is 1 ℃ / min, the second temperature is 500 ℃, and the reaction time in the ammonia atmosphere is 2 h.
4. The preparation method according to claim 2, characterized in that, In step (5), the volume fraction of H2 in the Ar / H2 mixed atmosphere is 5%–10%, the third temperature is 400 ℃, the reduction time is 2 h, and the heating rate is 5 ℃ / min.
5. A Co4N-Nv nanozyme prepared by any one of the preparation methods described in claims 2-4.
6. The application of the Co4N-Nv nanozyme as described in claim 1 or 5 as a lactate oxidase mimic in the catalytic oxidation of lactate.
7. A sweat lactic acid sensor, comprising: Working electrode, reference electrode, and counter electrode, wherein: The working electrode is a laser-etched graphene electrode, and the surface of the working electrode is sequentially modified with a Prussian blue electron mediator layer, a Co4N-Nv nanozyme catalytic layer and a chitosan protective layer. The Prussian blue electron mediator layer was obtained by cyclic voltammetry deposition. The deposition solution was a mixed solution containing 2.5 mM FeCl3, 2.5 mM K3Fe(CN)6, 100 mM KCl and 100 mM HCl. The scan rate was 50 mV / s and the number of scan cycles was 20. The Co4N-Nv nanozyme is as described in claim 1 or 5.
8. The sweat lactic acid sensor according to claim 7, wherein: The Co4N-Nv nanozyme catalytic layer was prepared by drop coating, with a drop coating amount of 2 µL, a concentration of 4 mg / mL, and a solvent of 0.1 M pH 7.4 phosphate buffer. The chitosan protective layer was formed by drop coating 3 µL of 1 wt% chitosan solution, with 2 wt% acetic acid as the solvent.
9. A method for detecting lactic acid, comprising: Using the sweat lactic acid sensor as described in claim 7 or 8, the current response value is recorded by chronoamperometry or cyclic voltammetry, and the lactic acid content in the sample is calculated based on the quantitative relationship between the current response value and the lactic acid concentration.
10. The lactic acid detection method according to claim 9, wherein: The test samples include sweat and other tissue fluids containing lactic acid. The detection limit is 0.065 mM, and the linear range is 5-30 mM. The electrochemical detection was performed in 0.1 M pH 7.4 phosphate buffer at a detection potential of 0.05 V.